Soluble Forms of the Subgroup A Avian Leukosis Virus [ALV(A)] Receptor Tva Significantly Inhibit ALV(A) Infection In Vitro and In Vivo - Holmen, Sheri L. (American Society for Microbiology, 1999)
The interactions between the subgroup A avian leukosis virus [ALV(A)] envelope glycoproteins and soluble forms of the ALV(A) receptor Tva were analyzed both in vitro and in vivo by quantitating the ability of the soluble Tva proteins to inhibit ALV(A) entry into susceptible cells. Two soluble Tva proteins were tested: the 83-amino-acid Tva extracellular region fused to two epitope tags (sTva) or fused to the constant region of the mouse immunoglobulin G heavy chain (sTva-mIgG). Replication-competent ALV-based retroviral vectors with subgroup B or C env were used to deliver and express the two soluble tv-a (stva) genes in avian cells. In vitro, chicken embryo fibroblasts or DF-1 cells expressing sTva or sTva-mIgG proteins were much more resistant to infection by ALV(A) (∼200-fold) than were control cells infected by only the vector. The antiviral effect was specific for ALV(A), which is consistent with a receptor interference mechanism. The antiviral effect of sTva-mIgG was positively correlated with the amount of sTva-mIgG protein. In vivo, the stva genes were delivered and expressed in line 0 chicken embryos by the ALV(B)-based vector RCASBP(B). Viremic chickens expressed relatively high levels of stva and stva-mIgG RNA in a broad range of tissues. High levels of sTva-mIgG protein were detected in the sera of chickens infected with RCASBP(B)stva-mIgG. Viremic chickens infected with RCASBP(B) alone, RCASBP(B)stva, or RCASBP(B)stva-mIgG were challenged separately with ALV(A) and ALV(C). Both sTva and sTva-mIgG significantly inhibited infection by ALV(A) (95 and 100% respectively) but had no measurable effect on ALV(C) infection. The results of this study indicate that a soluble receptor can effectively block infection of at least some retroviruses and demonstrates the utility of the ALV experimental system in characterizing the mechanism(s) of viral entry.